TRANSLANGUAGING: STUDENTS AS MEANING MAKING CONTRIBUTORS - Ahmad, Shahzad (International Journal of Language and Literary Studies, 2024)
Contrary to Communicative Language Teaching ideology, translanguaging exploits the collective linguistic output that potentially adds to the language learning capacity of learners. It has emerged as an empowering tool for bi/multilingual learners of a language. The following research questions will be asked: 1) How can translanguaging enrich students’ writing skills in the Target Language (TL)? 2) What are the drawbacks that may be encountered? 3) How does translanguaging go beyond the conventional approach to classroom learning? The study will focus on the mixed method approach employing a semi structured questionnaire and interviews. Anderson’s (2017 as cited in Turnbull, 2019) translanguaging continuum will be used as a reference point for this research. The results will be collated to examine the difference in responses and to see which strategy produces more favourable outcomes. This study will help to legitimize the use of translanguaging in the classroom as a means of maximizing students' potential of meaning-making activity.